PERANAN EKOLOGIS SPONS PADA EKOSISTEM TERUMBU KARANG - Tri Aryono Hadi (OSEANA, 2018)
ECOLOGICAL ROLES OF SPONGES IN CORAL REEF ECOSYSTEMS. Sponges are one of main reef benthic components which is quite abundant and worldwide distributed. Due to its unique characteristics, such as filtering water column, possessing pores throughout the body, and producing metabolite compounds, sponges play important roles in marine ecosystems. In coral reef ecosystems, the roles are very complex, including facilitating nutrient cycles, stabilizing/eroding calcareous substrates, hosting many types of marine organisms, providing protection to its symbions, competing with other marine benthos in structuring the reefs and as a bioindicator. In this case, sponges can be illustrated as a mediator between abiotic and biotic factors, thus material and energy transfers in the coral reef ecosystems can be boosted. Therefore, it is essential to monitor sponge communities in the reefs considering that its immense roles cannot likely be replaced by other marine organisms.